On the possibility of using CORONA and Landsat data for evaluating and mapping long-term LULC: Case study of Iraqi Kurdistan. (January 2018) - Saleem, A.; Corner, R.; Awange, J.
Abstract: Modern land development is regarded as having begun in the 1960s and since then the pattern of land cover has changed considerably in many parts of the world. The majority of change detection studies have used Landsat MSS, TM, ETM+, and Landsat LDCM imagery and other satellite imagery to quantify and map land use changes for many parts of the globe from the early 1970s. In most applications however, (e.g., Balcik, Sanli, Goksel, Ulugtekin, & Dogru, 2009) land use changes dating back to the 60s are desirable. Given that most images start from the 70s, one possibility of overcoming this is to extend the timeline of change detection analysis beyond the first Landsat satellite imagery by cross-referencing with CORONA imagery to include the 1960s. The main objective of this study is to employ CORONA and Landsat images to perform change detection analysis using the Kurdistan region as a case study. Kurdistan region covers an area of 44957.1 km 2 and the study period ranges from 1969 to 2014. The results of the maximum likelihood classification process for CORONA images show that these images may be classified successfully and accurately, showcasing the fact that the timeline of change detection analysis may be extended by using CORONA's unique historical images to include the period prior to the start of Landsat missions in 1972. For Kurdistan region, CORONA played a pivot role as baseline map as many of the changes occurred after 1974, when the Kurdish revolution ended. Its land use and land cover changes have been significant and may be divided into three stages: the first stage involves the destruction and demolition of the landscape between 1974 and 1991. The second stage is the stage of Kurdish freedom and peace involving minor changes in the landscape of the Kurdistan region that began in 1992 and lasted until 2002. Finally, the last stage is between late 2003 and the present date, period which, economic growth and population increase were the main factors influencing urban growth in the Kurdistan region. A positive non-linear relationship (R 2 = 0.89) was found between population increase and urban growth using regression analysis for the study area during period 1969 to 2014. This case study therefore highlights the possibility of combining both CORONA and Landsat to study LULC change of any region prior to 1970s. Highlights: Create new input data for the CORONA images for semi-auto classification process. CORONA image can extend the time-line starting from 1960s rather than 1970s. Classified CORONA image with high level of accuracy. Mapping LULC changes for long-term for the new study area (Kurdistan region). Organised army operations can make the changes in the landscape beside normal human's activities.